The Influence of Debt Policy, Profitability and Firm Size on Firm Value with Free Cash Flow as a Moderating Variable on the Kompas100 Index on the Indonesian Stock Exchange 2019-2023 - Nelly Sugianti; Laila Wardani; Siti Sofiyah (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to identify factors that influence firm value, such as debt policy, profitability, and firm size, with free cash flow as a moderating variable. The indicators in this study, namely firm value is proxied by Tobin's Q, debt policy is proxied by Debt to Equity Ratio (DER), profitability is proxied by Return on Asset (ROA), Firm Size, and Free Cash Flow (FCF). The population in this study were Kompas100 Index companies on the Indonesia Stock Exchange for five years (2019-2023), which were 100 companies. This study is quantitative. The data collection technique used purposive sampling. Based on this, 22 samples with 110 observations were obtained. The data analysis technique used panel data regression analysis and Moderate Regression Analysis (MRA) with Eviews 13 software. The results showed that debt policy had no significant effect on firm value, profitability had a positive effect on firm value, and firm size had a negative effect on firm value. Free cash flow can moderate the relationship between profitability and firm value, but cannot moderate the effect of debt policy and firm size on firm value.